Changes in the Plethysmographic Perfusion Index During an End-Expiratory Occlusion Detect a Positive Passive Leg Raising Test*. Issue 2 (February 2021) - Beurton, Alexandra; Gavelli, Francesco; Teboul, Jean-Louis; De Vita, Nello; Monnet, Xavier
Abstract : Objectives: The end-expiratory occlusion test for assessing preload responsiveness consists in interrupting mechanical ventilation for 15 seconds at end-expiration and measuring the cardiac index changes. The perfusion index is the ratio between the pulsatile and the nonpulsatile portions of the plethysmography signal and is, in part, determined by stroke volume. We tested whether the end-expiratory occlusion-induced changes in perfusion index could detect a positive passive leg raising test, suggesting preload responsiveness. Design: Observational study. Setting: Medical ICU. Patients: Thirty-one ventilated patients without atrial fibrillation. Interventions: We measured perfusion index (Radical-7 device; Masimo Corp., Irvine, CA) and cardiac index (PiCCO2 ; Pulsion Medical Systems, Feldkirchen, Germany) before and during a passive leg raising test and a 15-second end-expiratory occlusion. Measurements and Main Results: In 19 patients with a positive passive leg raising test (increase in cardiac index ≥ 10%), compared to the baseline value and expressed as a relative change, passive leg raising increased cardiac index and perfusion index by 17% ± 7% and 49% ± 23%, respectively, In these patients, end-expiratory occlusion increased cardiac index and perfusion index by 6% ± 2% and 11% ± 8%, respectively. In the 12 patients with a negative passive leg raising test, perfusion index did not significantly change during passive leg raising and end-expiratory occlusion. Relative changes in perfusion index and cardiac index observed during all interventions were significantly correlated ( r = 0.83). An end-expiratory occlusion-induced relative increase in perfusion index greater than or equal to 2.5% ([perfusion index during end-expiratory occlusion–perfusion index at baseline]/perfusion index at baseline × 100) detected a positive passive leg raising test with an area under the receiver operating characteristic curve of 0.95 ± 0.03. This threshold is larger than the least significant change observed for perfusion index (1.62% ± 0.80%). Conclusions: Perfusion index could be used as a reliable surrogate of cardiac index for performing the end-expiratory occlusion test. Confirming previous results, the relative changes in perfusion index also reliably detected a positive passive leg raising test. Abstract : Supplemental Digital Content is available in the text.